Twenty-Seven Tamoxifen-Inducible iCre-Driver Mouse Strains for Eye and Brain, Including Seventeen Carrying a New Inducible-First Constitutive-Ready Allele. Issue 4 (14th February 2019) - Korecki, Andrea J; Hickmott, Jack W; Lam, Siu Ling; Dreolini, Lisa; Mathelier, Anthony; Baker, Oliver; Kuehne, Claudia; Bonaguro, Russell J; Smith, Jillian; Tan, Chin-Vern; Zhou, Michelle; Goldowitz, Daniel; et al.
Abstract: To understand gene function, the cre/loxP conditional system is the most powerful available for temporal and spatial control of expression in mouse. However, the research community requires more cre recombinase expressing transgenic mouse strains (cre-drivers) that restrict expression to specific cell types. To address these problems, a high-throughput method for large-scale production that produces high-quality results is necessary. Further, endogenous promoters need to be chosen that drive cell type specific expression, or we need to further focus the expression by manipulating the promoter. Here we test the suitability of using knock-ins at the docking site 5′ of Hprt for rapid development of numerous cre-driver strains focused on expression in adulthood, using an improved cre tamoxifen inducible allele (icre/ERT2), and testing a novel inducible-first, constitutive-ready allele (icre/f3/ERT2/f3). In addition, we test two types of promoters either to capture an endogenous expression pattern (MaxiPromoters), or to restrict expression further using minimal promoter element(s) designed for expression in restricted cell types (MiniPromoters). We provide new cre-driver mouse strains with applicability for brain and eye research. In addition, we demonstrate the feasibility and applicability of using the locus 5′ of Hprt for the rapid generation of substantial numbers of cre-driver strains. We also provide a new inducible-first constitutive-ready allele to further speed cre-driver generation. Finally, all these strains are available to the research community through The Jackson Laboratory.